A longitudinal study of multidimensional performance characteristics related to physical capacities in youth handball - Matthys, S. P. J.; Vaeyens, R.; Fransen, J.; Deprez, D.; Pion, J.; Vandendriessche, J.; Vandorpe, B.; Lenoir, M.; Philippaerts, R. (Journal of Sports Sciences, 2013)
Longitudinal research provides valuable information about change and progress towards elite performance. Unfortunately, there is a lack of longitudinal research in handball. In this study, 94 youth handball players (oldest group: n = 41; age 15-17 and youngest group: n = 53; age 13-15) were followed over a three-year period. Repeated Measures ANCOVA was conducted to reveal longitudinal changes in anthropometry and physical performance between elite and non-elite players, controlling for maturation. Maturation effects were found for anthropometry (P < 0.01) and some physical performance measures in strength and speed (P < 0.05). The lack of significant interaction effects revealed that during the three years of the study the elite players did not improve their physical performance more rapidly than the non-elites. Furthermore, they had a similar anthropometric profile to the non-elites. Elite players performed better on the Yo-Yo Intermittent Recovery test (P < 0.01; on average 24.0 in the youngest group and 25.2% in the oldest group over the three years) and on the speed and coordination items (P < 0.05; shuttle run: 3.6 and 5.1%; cross hopping: 11.0 and 14.8%, handball-specific shuttle run: 7.6 and 7.7%; slalom dribble test: 10.7 and 8.9%; sprint 30 m: 4.9 and 3.9%). Additionally, Yo-Yo performance and coordination with and without a ball were the most discriminating factors between the playing levels. In conclusion, youth coaches and scouts within team handball should recognise the importance of good skills and an excellent endurance for talent identification purposes.